2016
DOI: 10.1186/s13195-016-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concomitant use of memantine on mortality and efficacy outcomes of galantamine-treated patients with Alzheimer’s disease: post-hoc analysis of a randomized placebo-controlled study

Abstract: BackgroundA large, prospective, 2-year, randomized study in patients with mild-to-moderate Alzheimer’s disease or mixed dementia demonstrated reductions in mortality and cognitive/functional decline in galantamine-treated patients. A post-hoc analysis was conducted to study the effect of (the presence or absence of) concomitant memantine use on treatment outcome.MethodsRandomized patients (N = 2045) were divided into subgroups based on memantine use. Analyses included demographic and clinical characteristics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…To assess whether subsequent articles for a given RCT reported sex-stratified data, we also considered the secondary articles. We found that in this group of 13 articles, [89][90][91][92][93][94][95][96][97][98][99][100][101] a sex-specific data analysis was present in 4 (30.8%). 91,92,99,100 Using a pooled data set from primary and secondary articles (Figure 3 and eFigure 2 in the Supplement), we found a statistically significant increasing temporal trend of articles that referenced a sex-specific data analysis in the methods (R, 0.30; 95% CI, 0.05-0.59; P = .03) and a similar trend for sex stratification in the results (R, 0.26; 95% CI, 0.01-0.55; P = .055).…”
Section: Reporting Of Sex-stratified Data and Its Temporal Trendmentioning
confidence: 69%
“…To assess whether subsequent articles for a given RCT reported sex-stratified data, we also considered the secondary articles. We found that in this group of 13 articles, [89][90][91][92][93][94][95][96][97][98][99][100][101] a sex-specific data analysis was present in 4 (30.8%). 91,92,99,100 Using a pooled data set from primary and secondary articles (Figure 3 and eFigure 2 in the Supplement), we found a statistically significant increasing temporal trend of articles that referenced a sex-specific data analysis in the methods (R, 0.30; 95% CI, 0.05-0.59; P = .03) and a similar trend for sex stratification in the results (R, 0.26; 95% CI, 0.01-0.55; P = .055).…”
Section: Reporting Of Sex-stratified Data and Its Temporal Trendmentioning
confidence: 69%
“…A combinação da memantina com inibidores da acetilcolinesterase pode ser utilizada no tratamento da AD devido aos dois mecanismos de ação atuarem de forma a melhorar o processo cognitivo do doente. (HAGER et al, 2016) O canabidiol (CBD) é uma substância da planta Cannabis sativa, não tem efeito psicotrópico e sua molécula atravessa livremente a barreira hematoencefálica, que é uma estrutura especial que envolve os vasos sanguíneos do sistema nervoso central e tem uma função metabólica importante, protegendo-o de substâncias potencialmente tóxicas.…”
Section: Farmácosunclassified
“…A 2-year randomized study showed a clinical benefit of galantamine in mild-to-moderate dementia patients in terms of reducing cognitive or functional decline, mortality and nursing home placement [ 76 ]. Surprisingly, a post hoc analysis of the same study revealed that such benefits were diminished in patients additionally taking memantine [ 77 ].…”
Section: Symptomatic Treatmentsmentioning
confidence: 99%